Effect of a structured educational intervention on family medicine residents’ knowledge of preconception and pregnancy nutrition: a pilot study - Gamze Sultan Güler; Saadet Tuba Çokkızgın; Raziye Şule Gümüştakım; Muhammed Semih Gedik; Muhammed Ali Güler; Seval Akben (Interdisciplinary Medical Journal, 2026)
Objective: The study evaluates the impact of educational intervention on family medicine residents’ knowledge regarding nutritional support during preconception and pregnancy. It aims to address knowledge deficiencies to enhance maternal-infant health outcomes. Method: The study followed a pre-test/post-test design, involving participants between October 1, 2024, and January 31, 2025. They first completed a digital questionnaire to determine pretraining knowledge levels, followed by an educational intervention. A posttraining assessment was conducted 15 days later to measure knowledge retention. Data were analyzed using SPSS v.15, and a significance level of p<0.05 was accepted. Results: A total of 48 participants were included before the training and 38 after the training, with mean ages of 33.67±7.19 and 34.03±7.34, respectively. No significant demographic differences were observed between the pretraining (n=48) and posttraining (n=38) groups (p>0.05). Before the training, 54.2% of participants stated that they had sufficient knowledge about nutrition during pregnancy, while after the training, this rate increased to 73.7%. The percentage of physicians who stated that they benefited from presentations and conferences as a source of information after the training was significantly higher than before the training at 89.5% (n=34) (p=0.001). Significant improvements were observed in knowledge related to folic acid and calcium supplementation, and routine vitamin-mineral requirements during pregnancy. Conclusion: Targeted training significantly improves family medicine residents’ knowledge of pregnancy-related nutrition and micronutrient supplementation. Supporting residency training with structured educational programs, online courses, and scientific meetings is recommended. Future studies should evaluate the long-term effects of such educational interventions